E. E. Cummings The Art of His Poetry - Friedman, Norman; Project Muse.; Project Muse. (2019)
In E. E. Cummings: The Art of His Poetry, Norman Friedman argues that critics who have focused on what Cummings's poetry lacks have failed to judge Cummings on his strengths. Friedman identifies a main strength of Cummings as his being a "sensual mystic." The book unpacks Cummings's subject matter, devices, and symbolism, ultimately helping readers develop a deeper understanding and appreciation of Cummings's work.
Introduction: Criticism -- Vision -- Action -- Voice -- Device -- Creation -- Growth -- Post-Script: 95 Poems -- Appendix -- Subject Index -- Index of First Lines
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Originally published as Johns Hopkins Press in 1967
Includes bibliographical references (pages 185-197) and indexes
Description based on print version record.
Keywords: Cummings, E. E. -- 1894-1962.; Cummings, E. E. -- 1894-1962 -- Criticism and interpretation; Electronic books; Criticism, interpretation, etc; Electronic books